Design and evaluation of scaring devices for the management of avian pests of oil palm (Elaeis guineensis Jacq.): DESIGN AND EVALUATION OF SCARING DEVICES FOR MANAGEMENT OF AVIAN PESTS OF OIL PALM - L SARAVANAN; POTINENI KALIDAS; T PHANIKUMAR; D DWARAKA KUMAR (Journal of Oilseeds Research, 2017)
Birds cause extensive damage to ripening oil palm fruits. Various methods and devices were evaluated for managing this menace in the past. The scaring devices designed in the present study using Compact Disks (CDs) proved effective in reducing the damage caused by avian pests on the ripening fruit bunches of oil palm. To increase the deterrent effect of CDs, the non-reflective sides were stuck with either red or yellow or black reflective radium sheets. Onto which two circular, concentric eye spots were designed and stuck horizontally. The CDs having circular eye spots stuck on red and yellow radium sheets protected the ripening fruit bunches from further damage by birds until harvest. The statistical analysis showed that the above treatments protected the ripening bunches from bird damage by 100 per cent. Protection was 97.2 per cent in the case of CDs having circular eye spots stuck on black radium sheets. CDs having no eye spots and radium sheet protected the bunches 84.6 per cent compared to control. This finding indicated that these devices could be effectively used judiciously to protect the ripening fruit bunches until harvest from avian pests in oil palm.